2017
DOI: 10.12659/msm.902770
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Ameliorates Post-Stroke Cognitive Deficits in Rats Through Histone Acetylation-Mediated Neurochemical Alterations

Abstract: BackgroundTo identify the effect of apigenin on cognitive deficits of rats after cerebral ischemia and reperfusion injury, and to investigate the potential molecular mechanisms.Material/MethodsThe rats were given sodium butyrate (NaB) or apigenin (20 or 40 mg/kg) for 28 days. Cognition was investigated by the Morris water maze (MWM) test. On day 28, the rats were euthanized and their hippocampal brain regions were used to identify biochemical and neurochemical alterations. The content of histone deacetylase (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…[41] reported that apigenin can significantly block colon cancer development by inhibiting tumor-specific pyruvate kinase M2 (PKM2)-mediated cellular glycolysis. Tu et al found that apigenin can remarkably improve cognitive deficits after reperfusion injury and cerebral ischemia via inhibition of histone deacetylase (HDAC) and promotion of brain-derived neurotrophic factor (BDNF) as well as synapsin-I (Syn-I) [42]. Another study by Fallatah O and his co-workers demonstrated the feasibility of apigenin on the therapy of plasmodium falciparum (P. falciparum) infectioninduced malarias [43].…”
Section: Discussionmentioning
confidence: 99%
“…[41] reported that apigenin can significantly block colon cancer development by inhibiting tumor-specific pyruvate kinase M2 (PKM2)-mediated cellular glycolysis. Tu et al found that apigenin can remarkably improve cognitive deficits after reperfusion injury and cerebral ischemia via inhibition of histone deacetylase (HDAC) and promotion of brain-derived neurotrophic factor (BDNF) as well as synapsin-I (Syn-I) [42]. Another study by Fallatah O and his co-workers demonstrated the feasibility of apigenin on the therapy of plasmodium falciparum (P. falciparum) infectioninduced malarias [43].…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin is a natural flavone present in vegetables and fruits such as celery, parsley, tea, onion and grapefruit [ 150 ]. Recent findings suggested that the molecule could also alleviate brain damage and ameliorate poststroke neurological and cognitive deficits in brain ischemia [ 151 , 152 ] and SAH [ 153 ] models. Apigenin protective effects seem to rely on multiple mechanisms involving the promotion of angiogenesis via caveolin-1/vascular endothelial growth factor (VEGF) pathway and reduction of TLR4-mediated inflammation [ 151 , 153 , 154 ].…”
Section: Polyphenols and Stroke: Results From Preclinical Stroke Mmentioning
confidence: 99%
“…Apigenin is a natural and common dietary flavonoid found in fruits and vegetables [32] and has become an attractive compound in cancer research because of its antitumor properties against many human cancer cell lines, including lung [33], colon, breast [34, 35], colon [36], and thyroid [37]. Recently, it was reported that apigenin attenuated oxidative stress of erythrocytes [38], suppressed oxidative stress-mediated apoptosis to play a protective role on the rotenone-induced rat model of Parkinson's disease [39], and attenuated OGD/R-induced neuronal injury mainly through histone acetylation-mediated neurochemical alterations [18]. Apigenin could attenuate apoptosis in HEK293 cells by modulating the caspase signal pathway [40], and alleviate endotoxin-induced myocardial toxicity by modulating oxidative stress, autophagy, and inflammation [5], although apigenin could induce apoptosis and autophagy to play a role in chemoprevention in several human cancer cell lines [41].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that Caveolin-1 decreased cerebral infarct volume, facilitated angiogenesis and neurogenesis, and promoted neurological recovery by upregulating the Caveolin-1/VEGF signaling pathway in a rat model of middle cerebral artery occlusion (MCAO) in our previous study [1517]. Apigenin ameliorates poststroke cognitive deficits through alteration of histone acetylation-mediated neurochemicals in vivo in another study [18]. Based on our previous study, we explored the effect of apigenin on the Caveolin-1/VEGF signaling pathway in an oxygen-glucose deprivation/reoxygenation (OGD/R) model of human brain microvascular endothelial cells (HBMVECs) and MCAO rat model.…”
Section: Introductionmentioning
confidence: 99%